Insights into the genomic and functional divergence of NAT gene family to serve microbial secondary metabolism - Sotiria Boukouvala; Evanthia Kontomina; Ioannis Olbasalis; Dionysios Patriarcheas; Dimosthenis Tzimotoudis; Konstantina Arvaniti; Aggelos Manolias; Maria-Aggeliki Tsatiri; Dimitra Basdani; Sokratis Zekkas (Scientific Reports, 2024)
Abstract Microbial NAT enzymes, which employ acyl-CoA to acylate aromatic amines and hydrazines, have been well-studied for their role in xenobiotic metabolism. Some homologues have also been linked to secondary metabolism, but this function of NAT enzymes is not as well-known. For this comparative study, we surveyed sequenced microbial genomes to update the list of formally annotated NAT genes, adding over 4000 new sequences (mainly bacterial, but also archaeal, fungal and protist) and portraying a broad but not universal distribution of NATs in the microbiocosmos. Localization of NAT sequences within microbial gene clusters was not a rare finding, and this association was evident across all main types of biosynthetic gene clusters (BGCs) implicated in secondary metabolism. Interrogation of the MIBiG database for experimentally characterized clusters with NAT genes further supports that secondary metabolism must be a major function for microbial NAT enzymes and should not be overlooked by researchers in the field. We also show that NAT sequences can be associated with bacterial plasmids potentially involved in horizontal gene transfer. Combined, our computational predictions and MIBiG literature findings reveal the extraordinary functional diversification of microbial NAT genes, prompting further research into their role in predicted BGCs with as yet uncharacterized function.